Analisis Penerapan Project Based Learning dalam Meningkatkan Pemahaman Konsep Pertidaksamaan Linear Satu Variabel - Rachma Cantika Damayanti; Tatang Herman; Aan Hasanah (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to analyze the effectiveness of implementing the Project-Based Learning (PjBL) model in improving students' understanding of Single Variable Linear Inequalities (PtLSV) in grade VII. Low conceptual understanding is evident from students' difficulties in modeling contextual problems, choosing solution procedures, and determining solution sets. This study used a descriptive qualitative method by conducting observations at a junior high school in Bandung through worksheets and interviews with teachers and students. The results of data analysis show that there is still a lack of significant improvement in the understanding of PtLSV concepts among students in the class. PjBL proved to be ineffective because, although it encouraged active involvement, teamwork, and students' ability to apply mathematical concepts in real contexts through project completion, there were still several shortcomings in students' understanding of inequality material. Therefore, improvements are still needed in the application of PjBL, especially in learning inequalities and other mathematical materials.